Beyond Help: diakonia in the Contemporary Church. Issue 8 (17th November 2019) - Ritchie, Angus
ABSTRACT: The argument of this paper is that, partly under the influence of a secularized conception of ethics, diakonia has often also been misconstrued as an activity done by a more privileged group to a needier one. It draws on the witness of the New Testament, and on contemporary Catholic thought, to argue for a vision of diakonia as a ministry exercised by, and not just for, the poorest – and offers Christian engagement in community organizing as an embodiment of that vision.